THE USAGE OF PAUSE PROCEDURE METHOD IN THE LECTURES AND POSITIVE AND NEGATIVE SIDES OF ITS IMPLEMENTATION - Turdiyeva Zahro Mirsoliyevna (TADQIQOTLAR, 2025)
The Pause Procedure teaching strategy has emerged as an effective method to enhance learning outcomes in lecture-based instruction. This strategy involves introducing short, structured pauses during lectures to provide students with opportunities to reflect, review, and engage actively with the material. Research demonstrates its effectiveness in improving comprehension, retention, and overall engagement. Studies by Ruhl, Hughes, and Schloss (1987), Bonwell and Eison (1991), and others highlight the strategy’s ability to break the monotony of traditional lectures, foster critical thinking, and create dynamic learning environments. This article explores the theoretical underpinnings, practical applications, and benefits of the Pause Procedure in lectures. Specific activities for implementing the strategy, such as peer discussions, note reviews, and quick assessments, are discussed in detail, alongside challenges and solutions for diverse educational contexts. The article concludes with evidence-based recommendations for integrating the Pause Procedure to maximize its potential in higher education.